Acoustic insulation characteristics of sandwich composite shell systems with double curvature: The effect of nature of viscoelastic core. (March 2023) - Seilsepour, Hasan; Zarastvand, Mohamadreza; Talebitooti, Roohollah
A viscoelastic model is proposed in this approach to determine the sound transmission loss coefficient of a sandwich shell system with double curvature. The structure is composed of a double-walled composite shell subjected to a viscoelastic core. Investigating the efficient impresses of rotary inertia and shear deformation, vibration equations of both outer and inner shells are extracted within the framework of shear deformation shallow shell theory. Besides, the Zener mathematical model is used for viscoelastic material, which is based on a spring connected in series with a parallel mixture of spring and dashpot. This model presents the dynamic response in the whole frequency domain at which shear modulus and bulk complex modulus are frequency dependent. Since the performed studies on the sound transmission loss of this kind of structures are insignificant, the outcomes of plate models with a viscoelastic core are used to provide a reliable sound transmission loss comparison. The results show that the applied strategy can improve the acoustic characteristics of the system at high frequencies compared to that of a single-layer one with the same mass. This issue is more highlighted while the thickness of the viscoelastic layer enhances, which confirms the positive performance of the viscoelastic materials in this range of frequency, particularly in the resonant frequency. In addition to the curvature effect on acoustic features, the vibration response of the system is configured based on various frequencies and materials.